(untitled) (Open Herald: Periodical of Methodical Research, 2023)
The primary purpose of this study was to determine the levels of challenges encountered and their coping mechanism among BSED students of Altavas College.The researchers collected the data by using an electronic web-based questionnaire through the Google survey tool (Google Forms) using questions made by the researchers. The survey comprised 2 subsections according to the participant’s challenges and a question corresponding to each respondent’s coping mechanism. The analysis was perceived using the frequency count, percentage, and mean. Descriptive analyses were done. The result showed on the level of challenges encountered of the respondents was “Very Challenge”. This signifies that the respondents are very challenge in Modular and Online Distance Learning. The level of coping mechanism of Bachelor in Secondary Education of Altavas College was described as “Very Highly Evident”. It impliesthat students are good in coping with the challenges they are facing in the modular and online distance learning.